Growth performance of Acacia species and Eurycoma longifolia Jack mixed planting on BRIS soils - Darus, Dasrul Iskandar (2012)
A study was undertaken to assess i) the growth performance of four years-old Acacia mangium, A. auriculiformis and Acacia hybrid trees on two different BRIS (Beach Ridges Interspersed with Swales) soil series, ii) the growth performance of three years old Eurycoma longifolia Jack trees mixed planting with Acacia spp on BRIS soil and iii) to study the soil nutrient, light penetration (gaps) and litterfall of the mixed Acacia spp. and Eurycoma longifolia stands planted on BRIS soil.